ANALISIS PENYEBAB TERJADI FALSE ALARM PADA FIRE ALARM SYSTEM DI GEDUNG NUSANTARA I DPR RI - Anggraeni, Destri; Hamid, Mustofa Abi (Teknika, 2024)
Workplace fire incidents can harm many parties, so a fire can cause fatalities, material losses, work losses, and other losses that can have fatal consequences. This research aims to understand the working principles of the fire detection system, determine the role of the fire alarm system in the security and safety of building occupants, and determine the causes of false alarms in the fire alarm system in the Nusantara I DPR RI Building. This research uses qualitative procedures with a descriptive approach. Information retrieval methods take the form of observation, interviews and documentation. The study showed that this fire warning system could detect and give a warning sound to all building occupants. This is due to a fire initiated by sending a signal from the detector and connected to the master panel. The role of a fire warning system in a building is to warn building occupants, workers or visitors about the presence of a fire so that they can immediately take appropriate evacuation action and extinguish the fire if possible. The factor that causes false alarms is that the detector in this fire alarm immediately detects things like cigarette smoke, dust, problems with the installation, and damaged detectors.